Fabrication and characterization of chitosan–gelatin–chondroitin sulfate-diclofenac scaffold with cross-linked glutaraldehyde for potential application in osteoarthritis - Wa Ode Nurfinti, Chrismawan Ardianto, Toetik Aryani, Mareta Rindang Andarsari, Anisa Cendekia Muslimah, Ita Pramudia Ananta, Yusuf Alif Pratama, Nour El Huda Abd Rahim, Sakinato Mazidda, Esti Hendradi, Junaidi Khotib, Fani Deapsari, Aniek Setiya Budiatin (Journal of Applied Pharmaceutical Science, 2025)
The inadequate regenerative capacity of cartilage renders osteoarthritis (OA) and cartilage injuries difficult to manage. In tissue engineering, a scaffold facilitates establishing an environment favorable to cell proliferation, migration, and adhesion. Moreover, diclofenac sodium can be administered locally due to the scaffold’s porous architecture, which possesses anti-inflammatory characteristics. This study investigated the development and characterization of an innovative scaffold formulation intended for potential application in cartilage repair associated with OA and cartilage injuries. The scaffold was cross-linked with varying concentrations of GA (0.00%–2.50%) and comprised chitosan, gelatin, chondroitin sulfate, and PEG 400. The scaffold also contained the anti-inflammatory agent, diclofenac sodium, which was dissolved in PEG 400 for targeted drug delivery. The pore diameter, porosity, compressive strength, and degradation of the scaffolds were assessed following their dried form. The results indicated that GA significantly influenced these attributes, with porosity, mechanical stability, and degradation control improved at an optimal concentration of 0.50 percent. GA cross-linking between polymer chains enhanced the scaffold’s integrity and augmented its mechanical properties through the establishment of more rigid structures. The cross-linking of the amino group in chitosan with the sulfonate group in chondroitin sulfate enhanced the scaffold’s stability. The study’s findings indicated that GA-optimized chitosan–gelatin–chondroitin sulfate-PEG 400-diclofenac scaffolds exhibited suitable physicochemical and mechanical properties, supporting their potential use in localized drug delivery systems for OA management.
Keywords: Cartilage, GA, neglected tropical disease, osteoarthritis, medicine